Experimental determination of zinc isotope fractionation in complexes with the phytosiderophore 2′-deoxymugeneic acid (DMA) and its structural analogues, and implications for plant uptake mechanisms - Marković, Tamara; Manzoor, Saba; Humphreys-Williams, Emma; Kirk, Guy J. D.; Vilar, Ramon; Weiss, Dominik J. (American Chemical Society, 2016)
The stable isotope signatures of zinc and other metals are increasingly used to study plant and soil processes. Complexation with phytosiderophores is a key reaction and understanding the controls of isotope fractionation is central to such studies. Here, we investigated isotope fractionation during complexation of Zn2+ with the phytosiderophore 2′-deoxymugeneic acid (DMA), and with three commercially available structural analogues of DMA: EDTA, TmDTA, and CyDTA. We used ion exchange chromatography to separate free and complexed zinc, and identified appropriate cation exchange resins for the individual systems. These were Chelex-100 for EDTA and CyDTA, Amberlite CG50 for TmDTA and Amberlite IR120 for DMA. With all the ligands we found preferential partitioning of isotopically heavy zinc in the complexed form, and the extent of fractionation was independent of the Zn:ligand ratio used, indicating isotopic equilibrium and that the results were not significantly affected by artifacts during separation. The fractionations (in ‰) were +0.33 ± 0.07 (1σ, n = 3), + 0.45 ± 0.02 (1σ, n = 2), + 0.62 ± 0.05 (1σ, n = 3) and +0.30 ± 0.07 (1σ, n = 4) for EDTA, TmDTA, CyDTA, and DMA, respectively. Despite the similarity in Zn-coordinating donor groups, the fractionation factors are significantly different and extent of fractionation seems proportional to the complexation stability constant. The extent of fractionation with DMA agreed with observed fractionations in zinc uptake by paddy rice in field experiments, supporting the possible involvement of DMA in zinc uptake by rice.